Complex mullerian duct anomaly in a young female with primary amenorrhoea, infertility, and chronic pelvic pain - Sanyal Kumar; Bhawna Satija; Leena Wadhwa (Wolters Kluwer Medknow Publications, 2012)
Mullerian duct anomalies, though rare, can be a treatable cause of pelvic pain and infertility. Various complex Mullerian duct anomalies may exist with combination of features of more than one class. Since there are no precise clinical or imaging criteria to enable specific categorisation, there is ambiguous classification of these anomalies by various radiologists and clinicians. A young female presented with complaints of chronic pelvic pain, primary amenorrhoea and infertility. The patient was evaluated by sonography and Magnetic Resonance Imaging and diagnosed as case of complex mullerian duct anomaly, a unicornuate uterus with cervical dysgenesis and cavitated, noncommunicating, rudimentary right horn. The findings were confirmed on laprohysteroscopy and the patient underwent hystertectomy. There should be an integrated clinico-radiological classification scheme and familiarity with rare and complex anomalies for appropriate diagnosis and management of complex Mullerian duct anomalies.